GENESIS AND EVOLUTION ОF THE POLITICAL THEOLOGY CONCEPT ОF CORPUS MYSTICUM IN MEDIEVAL THEOLOGICAL АND POLITICAL THOUGHT - Haiko, Oleg (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
This article examines the genesis and evolution of the medieval politico-theological concept of corpus mysticum. It shows how the concept of corpus Christi became established in Christian theology under the influence of early Christian authors. Particular attention is paid to the Carolingian Eucharistic controversies of the ninth century, which contributed to a more systematic understanding of corpus Christi and led to the gradual consolidation in medieval theology of the terminological distinction between corpus verum and corpus mysticum. The article analyzes the key ideas of Paschasius Radbertus and Ratramnus of Corbie, whose positions during the Carolingian Eucharistic debates significantly influenced the later conceptualization of corpus mysticum in medieval theology. The study also traces the impact of the eleventh-century Eucharistic crisis, which led to a terminological inversion whereby the term corpus verum increasingly came to designate the Eucharist, while corpus mysticum was gradually applied to the Church. The role of Peter Lombard in consolidating the use of corpus mysticum as a designation for the Church within scholastic and university theology is examined. It is argued that the spread of the theory of corporate bodies in the thirteenth century further contributed to the stabilization of the concept, since this theory provided a juridical framework for understanding a community as a single corporate subject. The article also highlights the institutional and political factors that strengthened the Roman Catholic Church and encouraged the use of corpus mysticum as a designation for the Church. Particular attention is given to Thomas Aquinas, whose work played a crucial role in the systematic formulation of the theological terminology describing the three modes of Christ’s presence and in establishing corpus mysticum as a synonym for the Church. Finally, the article demonstrates that the development of the theory of corporate bodies and the gradual centralization of royal authority in the Late Middle Ages led to important semantic transformations. The term corpus mysticum gradually lost its exclusive association with the Roman Catholic Church and came to function as a more general designation for corporate entities. As a result, a concept that originally belonged to theological discourse began to be widely used in a politico-legal sense, while the term corpus politicum increasingly replaced corpus mysticum as the preferred designation for the kingdom. The article also examines the role of medieval canonists in the processes of universalization and secularization of the concept of corpus mysticum.